Coping with Higher Oil Prices - Bacon, Robert; Kojima, Masami (World Bank, Washington, DC, 2014)
The rise in oil prices and the associated increase in the prices of petroleum products that has occurred since the beginning of 2004 are having adverse effects on the users of petroleum products in all countries. In many developing countries, price increases have generated considerable pressure for government response to lessen the burden of higher world oil prices, and policies to minimize budgetary support have met with fierce opposition. The individual characteristics of petroleum products strongly influence the way consumers react to various policies that might be tried. Some policy measures that are effective for other items for the purpose of protecting consumers, and especially the poor, from price increases are not necessarily suitable or effective for petroleum products.